2001
DOI: 10.1073/pnas.241349398
|View full text |Cite
|
Sign up to set email alerts
|

A transcription factor regulatory circuit in differentiated pancreatic cells

Abstract: Mutations in the human genes encoding hepatocyte nuclear factors (HNF) 1␣, 1␤, 4␣, and IPF1(PDX1͞IDX1͞STF1) result in pancreatic ␤ cell dysfunction and diabetes mellitus. In hepatocytes, hnf4␣ controls the transcription of hnf1␣, suggesting that this same interaction may operate in ␤ cells and thus account for the common diabetic phenotype. We show that, in pancreatic islet and exocrine cells, hnf4␣ expression unexpectedly depends on hnf1␣. This effect is tissue-specific and mediated through direct occupation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
222
1
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(239 citation statements)
references
References 39 publications
14
222
1
2
Order By: Relevance
“…The P2 promoter contains functional binding sites for the MODY transcription factors HNF-1α, HNF-1β and Pdx1/IPF1, and was proposed to serve as a positive cross-regulatory feedback circuit between HNF-1α and HNF-4α in human pancreatic cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…The P2 promoter contains functional binding sites for the MODY transcription factors HNF-1α, HNF-1β and Pdx1/IPF1, and was proposed to serve as a positive cross-regulatory feedback circuit between HNF-1α and HNF-4α in human pancreatic cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…In ␤-cells, HNF-3␤ and HNF-1␣ may directly regulate PDX-1 gene transcription (10)(11)(12)(13)(14)(15). In addition, HNF-1␣ and HNF-4␣ autoregulate each other's expression (14,16). Interestingly, in contrast to humans, only heterozygous Pdx-1 mutants but not Hnf-4␣, Hnf-1␣, Hnf-1␤, or Beta2 induce a diabetic phenotype in mice, presumably because of the direct importance of Pdx-1 in regulating glucose transporter 2 (Glut-2), glucokinase (Gck), and insulin gene expression.…”
mentioning
confidence: 99%
“…It is not clear whether PDX-1 directly regulates the expression of the HNF-1α gene transcription; therefore the regulation of HNF-1α by other transcription factors should be examined. Recent studies have suggested that HNF-1α regulation in the pancreas is more complex rather than a simple linear hierarchy [47,48].…”
Section: Discussionmentioning
confidence: 99%